An investigation of the time period within which frozen-thawed semen delivers a high conception rate in lactating dairy cows - Toshiaki SUMIYOSHI; Tomomi TANAKA; Hideo KAMOMAE (The Society for Reproduction and Development, 2020)
We determined the length of time within which frozen-thawed semen delivered a high conception rate in present-day lactating dairy cows. The cows utilized were a total 100 milking Holstein-Friesian cows kept in tie-stall style farms. We carried out artificial insemination (AI) during the periovulatory period at a predicted time based on ovulation, and checked ovulation at 6-h intervals after AI. The period from AI to ovulation ranged from 48 h (i.e., 48 h before ovulation) to -12 h (i.e., 12 h after ovulation). High conception rates averaging 63.0% were obtained by carrying out AI > 6-30 h before ovulation, significantly higher than the conception rates of 30.0% (P < 0.05) and 26.9% (P < 0.01) from AI carried out earlier than 30 h before ovulation and later than 6 h before ovulation, respectively. It was concluded that frozen-thawed semen delivers a conception rate of ≥ 60% for > 24-30 h after AI, and that a conception rate of ≥ 60% can be achieved by carrying out AI 6-30 h before ovulation using frozen-thawed semen.